2020
DOI: 10.2147/dddt.s225220
|View full text |Cite
|
Sign up to set email alerts
|

<p>Safety, Tolerability, and Pharmacokinetics of Adrenomedullin in Healthy Males: A Randomized, Double-Blind, Phase 1 Clinical Trial</p>

Abstract: Background: Adrenomedullin (AM), an endogenous vasodilative peptide, has immunomodulative effects and acts as an accelerator of mucosal regeneration in the digestive tract. AM has shown beneficial effects in rodent models of inflammatory bowel disease and patients with ulcerative colitis. The present study aimed to evaluate the pharmacodynamic properties and safety of AM in healthy male adults in a phase 1 clinical trial. Methods: This phase 1, randomized, double-blind, single-center study was conducted on hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 27 publications
(29 reference statements)
3
25
0
Order By: Relevance
“…The increased plasma concentration of AM mostly returned to basal levels within 2 h after the termination of the AM infusion. We did not observe any progressive increase in the plasma concentration of AM after repeated administrations, which is a concern in multiple-dose administration studies in a phase 1 trial [ 15 ]. The AUC 0-10 h after 14 days of the three groups, namely 5, 10, and 15 ng/kg/min groups, was shown to be 152 ± 34, 281 ± 39, and 440 ± 191 h*pg/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The increased plasma concentration of AM mostly returned to basal levels within 2 h after the termination of the AM infusion. We did not observe any progressive increase in the plasma concentration of AM after repeated administrations, which is a concern in multiple-dose administration studies in a phase 1 trial [ 15 ]. The AUC 0-10 h after 14 days of the three groups, namely 5, 10, and 15 ng/kg/min groups, was shown to be 152 ± 34, 281 ± 39, and 440 ± 191 h*pg/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…AM is thought to work as an endogenous counter-factor for UC, and thus, increases in AM production in UC patients were suggested. We found that the basal plasma concentration of AM was higher in patients with UC than that in healthy volunteers in the phase 1 single-dose study (11.4 ± 7.2 pg/mL ( n = 20) vs. 7.2 ± 1.4 pg/mL ( n = 23); P < 0.0001) [ 15 ]. Of note, in one UC patient in the present study, this value was found to be below the lower limit of quantification (< 5 pg/mL).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations